The Effect of Before and After Getting Tax Education on Tax Compliance - Fakhral Nisa; Dedi Kurniawan (Journal of Applied Accounting and Taxation, 2023)
Tax education is needed to fulfill the level of community compliance with taxation. To increase obedient behavior, taxpayers must understand tax regulations. This study aims to test whether there is an influence before and after getting a tax education. This research uses a quantitative approach using experimental research. The total number of respondents in this study was 62. The data collection method of this study used a questionnaire distributed via Google Forms. The result of the research is that there is a difference in tax compliance after and before getting a tax education.